2008
DOI: 10.1073/pnas.0711743105
|View full text |Cite
|
Sign up to set email alerts
|

Role of catalysts in dehydrogenation of MgH 2 nanoclusters

Abstract: A fundamental understanding of the role of catalysts in dehydrogenation of MgH2 nanoclusters is provided by carrying out firstprinciples calculations based on density functional theory. It is shown that the transition metal atoms Ti, V, Fe, and Ni not only lower desorption energies significantly but also continue to attract at least four hydrogen atoms even when the total hydrogen content of the cluster decreases. In particular, Fe is found to migrate from the surface sites to the interior sites during the deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 30 publications
(25 reference statements)
3
54
1
Order By: Relevance
“…Simulation has also demonstrated that nanoscale (MgH 2 ) n clusters, cut from the bulk, also possess lower dehydrogenation enthalpies than the bulk. 17,18,19,20 Interestingly however, in these simulations only very small clusters (n = 1 to 4) possess lower dehydrogenation enthalpies than the bulk, larger clusters actually possess dehydrogenation enthalpies greater than that of the bulk, nanostructuring will only improve thermodynamic properties if it is possible to synthesize MgH 2 as molecular-size units, larger units are less stable than the bulk. At the nanoscale, it is well-known that cluster structures can be vastly different from the bulk, strongly modifying energetics.…”
Section: : Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation has also demonstrated that nanoscale (MgH 2 ) n clusters, cut from the bulk, also possess lower dehydrogenation enthalpies than the bulk. 17,18,19,20 Interestingly however, in these simulations only very small clusters (n = 1 to 4) possess lower dehydrogenation enthalpies than the bulk, larger clusters actually possess dehydrogenation enthalpies greater than that of the bulk, nanostructuring will only improve thermodynamic properties if it is possible to synthesize MgH 2 as molecular-size units, larger units are less stable than the bulk. At the nanoscale, it is well-known that cluster structures can be vastly different from the bulk, strongly modifying energetics.…”
Section: : Introductionmentioning
confidence: 99%
“…Substitutional doping of nickel onto magnesium sites of the MgH 2 crystal has been demonstrated to reduce dehydrogenation thermodynamics. 18,25 Interstitial doping sites for Ni dopants are lower in energy, 54 however upon complete dehydrogenation to Mg the Ni interstitials would migrate to fill Mg vacancies. As the (MgH 2 ) n clusters present radically different structural motifs to the bulk, it is expected that the defect formation energies are also different.…”
Section: 2: Nickel Dopingmentioning
confidence: 99%
“…The obtained cohesion was larger than experimentally observed which is an indication of the covalent bonding contribution to MgH 2 [49]. Although each of the aforementioned calculations [42,44,[48][49][50][51][65][66][67][68][69][70][71][72] give some information, a complete and coherent explanation of numerous experimental findings has not been found.…”
Section: Introductionmentioning
confidence: 50%
“…Here we will briefly outline the influence of transition metal (TM) impurities on the Mg/MgH 2 system properties. Extensive experimental [3,4,[6][7][8]44,[55][56][57][58][59][60][61][62] and theoretical (computational) [21,44,[67][68][69][70][71][72]91,[93][94][95][96][97][98] investigations have been devoted to the subject, and the importance of the TM(d)-H(s) interaction for the TM catalytic properties [67,71,72,93,95,96] established. To illustrate this, the difference between the center of the TM 3d-band and H(s) level, and its position relative to the 3d-band [99], are presented in Figure 8.…”
Section: Possibilities For Improvement Of the Mg/mgh 2 Hydrogenation/mentioning
confidence: 99%
See 1 more Smart Citation